Peer-to-peer power trading with voltage and congestion management for distribution grids - Sampath, Lahanda Purage Mohasha Isuru (2021)
In this work, a novel distribution grid level peer-to peer (P2P) power market framework is proposed. The proposed market framework enables the satisfaction of distribution grid constraints such as the voltage limits and transfer capacity limits, for all P2P power transactions between each producer-consumer pair. An Alternating direction method of multipliers (ADMM)- based coordinating algorithm is proposed in which the P2P power trading is facilitated at the first step, and the second step involves ancillary services market clearing considering the grid constraints and the power injections of the P2P participants, in a distributed and interactive manner. The distribution locational marginal prices are iteratively computed in the process so that the costs associated with P2P energy transactions are allocated to the respective producer-consumer pairs. As such, the proposed algorithm enables optimal P2P power trading while supporting optimal voltage and congestion management of the distribution grid. The case studies illustrate the effectiveness of the proposed ADMM-based coordination algorithm.